ANALISIS KAPASITAS KEBUTUHAN LAHAN PARKIR DI MAKAM BUNG KARNO, KOTA BLITAR - Sa'dillah, M.; Primasworo, Rifky Aldila; Bulu, Kristian (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2025)
The Bung Karno Tomb Area requires adequate parking facilities to accommodate two-wheeled, four-wheeled, dan six-wheeled vehicles. A viral case regarding a parking fee of up to IDR 800,000 for a group of buses at the Bung Karno Tomb Tourism dan Trade Information Center (PIPP) highlights the importance of clear dan transparent parking management (Metrotvnews 2025). This study employs a quantitative approach to analyze parking space requirements dan propose solutions for parking area management. The analysis shows a total of 627 parked vehicles, with an average parking volume of 647 vehicles dan an accumulation of 54 vehicles. The average parking duration is 13 minutes for two-wheeled vehicles, 5 minutes for four-wheeled vehicles, dan 6 minutes for heavy vehicles. Based on data from 100 respondents, 54% were male dan 46% were female, with the highest rate of private vehicle ownership among male respondents. These findings indicate that the increasing mobility of visitors must be balanced with more efficient parking arrangements. Therefore, well-planned dan capacity-appropriate parking management solutions are essential to improve visitor comfort, reduce congestion in the tourist area, dan strengthen the positive image of the Bung Karno Tomb Area as a leading tourist destination in Blitar City.